Voluntary Medical Male Circumcision for HIV Prevention in Swaziland: Modeling the Impact of Age Targeting. - Katharine Kripke; Velephi Okello; Vusi Maziya; Wendy Benzerga; Munamato Mirira; Elizabeth Gold; Melissa Schnure; Sema Sgaier; Delivette Castor; Jason Reed; Emmanuel Njeuhmeli (PLoS ONE, 2016)
BACKGROUND:Voluntary medical male circumcision (VMMC) for HIV prevention has been a priority for Swaziland since 2009. Initially focusing on men ages 15-49, the Ministry of Health reduced the minimum age for VMMC from 15 to 10 years in 2012, given the existing demand among 10- to 15-year-olds. To understand the implications of focusing VMMC service delivery on specific age groups, the MOH undertook a modeling exercise to inform policy and implementation in 2013-2014. METHODS AND FINDINGS:The impact and cost of circumcising specific age groups were assessed using the Decision Makers' Program Planning Tool, Version 2.0 (DMPPT 2.0), a simple compartmental model. We used age-specific HIV incidence from the Swaziland HIV Incidence Measurement Survey (SHIMS). Population, mortality, births, and HIV prevalence were imported from a national Spectrum/Goals model recently updated in consultation with country stakeholders. Baseline male circumcision prevalence was derived from the most recent Swaziland Demographic and Health Survey. The lowest numbers of VMMCs per HIV infection averted are achieved when males ages 15-19, 20-24, 25-29, and 30-34 are circumcised, although the uncertainty bounds for the estimates overlap. Circumcising males ages 25-29 and 20-24 provides the most immediate reduction in HIV incidence. Circumcising males ages 15-19, 20-24, and 25-29 provides the greatest magnitude incidence reduction within 15 years. The lowest cost per HIV infection averted is achieved by circumcising males ages 15-34: $870 U.S. dollars (USD). CONCLUSIONS:The potential impact, cost, and cost-effectiveness of VMMC scale-up in Swaziland are not uniform. They vary by the age group of males circumcised. Based on the results of this modeling exercise, the Ministry of Health's Swaziland Male Circumcision Strategic and Operational Plan 2014-2018 adopted an implementation strategy that calls for circumcision to be scaled up to 50% coverage for neonates, 80% among males ages 10-29, and 55% among males ages 30-34.